Molecular Characterization of EMM-Like Genes in the MGA Regulon of Group A Streptococcus Strain ST4547 - Eshaghi, Majid (2001)
Sequence analysis of the 5' region of the emm gene was employed to differentiate 39 group A streptococci (GAS) isolates collected between 1989 to 1997 from patients and carriers in Kuala Lumpur. Sixty-one percent (24) of these isolates contained emm genes encoding the M protein for which M-antigen associations had not been made. The remaining strains bad emm sequences in agreement with previously recorded M-antigen associations. In some cases antigenic variations were observed among individual M types as well as the isolates tested compared to published M protein sequences. These differences were predominantly due to the non-synonymous base substitutions and occasionally, short insertions and deletions Nucleotide sequencing of the mga regulon of a new Malaysian emm type ST4547 group A streptococcus an opacity factor (OF) negative isolate, showed the existence of two emm-like genes, emm and mrp. The emm gene encoded the M protein whereas mrp gene encoded the IgG Fc receptor. The gene located upstream of the scpA gene, comprised 1305 nucleotides encoded a M protein of 435 amino acids in length with a predicted molecular weight of 49.0 kDa or a predicted mature protein of 394 amino acids with a molecular weight of 44. 7 kDa. At the upstream of this gene and downstream of mga gene another gene was found and designated as mrpST4547. The sequence of this gene comprised 1 167 nucleotides encoded a predicted protein of 388 amino acids in length with a predicted molecular weight of 42.2 kDa or a predicted mature protein of 347 amino acids with a molecular weight of 31.9 kDa. The mga regulon of the strain ST4547 had a mosaic structure consisting of DNA segments which were suggested to had originated from different OF positive and OF negative strains. The sequences flanking the hypervariable and C repeats of the emmST4547 gene showed high similarity to a corresponding region in the mga regulon of OF positive strains notably M15, M4, M22 and M50. In contrast, the sequence of the hypervariable and C repeats region of the emmST4547 gene revealed high similarity to equivalent regions in the OF negative strains. These data suggested that horizontal transfer of emm-like genes could occur between OF positive and OF negative strains resulting in divergence in the architecture of the mga regulon. This study showed that sequencing of the 5' region of the emm gene of GAS isolates was effective for surveying the sequence variability of the M protein and useful for monitoring GAS strain diversity in Malaysia as well as showing the mechanisms involved for antigenic diversity in M proteins. This study also il1ustrated a new mosaic in structure of mga regulon of OF negative strains with existence of mrp and emm genes. As far as this research was concerned to our knowledge, such a study has been done for the first time in a developing country.